Full throttle [compact disc, unabridged] : stories - Hill, Joe; King, Stephen, 1947- (Harper Audio, 2019)
"In this masterful collection of short fiction, Joe Hill dissects timeless human struggles in thirteen relentless tales of supernatural suspense, including "In The Tall Grass," one of two stories co-written with Stephen King, basis for the terrifying feature film from Netflix. A little door that opens to a world of fairy tale wonders becomes the blood-drenched stomping ground for a gang of hunters in "Faun." A grief-stricken librarian climbs behind the wheel of an antique Bookmobile to deliver fresh reads to the dead in "Late Returns." In "By the Silver Water of Lake Champlain," two young friends stumble on the corpse of a plesiosaur at the water's edge, a discovery that forces them to confront the inescapable truth of their own mortality, and other horrors that lurk in the water's shivery depths. And tension shimmers in the sweltering heat of the Nevada desert as a faceless trucker finds himself caught in a sinister dance with a tribe of motorcycle outlaws in "Throttle," co-written with Stephen King. Featuring two previously unpublished stories, and a brace of shocking chillers, Full Throttle is a darkly imagined odyssey through the complexities of the human psyche. Hypnotic and disquieting, it mines our tormented secrets, hidden vulnerabilities, and basest fears, and demonstrates this exceptional talent at his very best"--